Development of a novel sensor for the detection of donepezil hydrochloride as Alzheimer's disease drug utilizing CuO-TiO2 hybrid nanostructures - Ye Zhu; Yueyan Huang (Alexandria Engineering Journal, 2024)
In this study, donepezil hydrochloride (DZ HCl), a crucial medication for the treatment of Alzheimer's disease, is detected using a new sensor built on CuO-TiO2 hybrid nanostructures. The sensor showed improved performance characteristics with a computed limit of quantitation of 0.211 and a limit of detection of 0.063. These qualities included improved stability, selectivity, and sensitivity. The fabrication process demonstrated repeatability, with a 4.27% relative standard deviation. After 10 successive readings, the sensor maintained 95% of its initial response, demonstrating its long-term stability. By quantifying DZ HCl in urine samples, the practical applicability of the sensor was confirmed. Remarkably, the sensor achieved a remarkable recovery rate of 97.00–99.41% and a suitable relative standard deviation range of 3.29–4.71%. The results of this work contribute to the development of trustworthy electrochemical sensors for medicinal chemicals and have prospective uses in pharmacological, biological, and therapeutic fields.